Online Loan Victims: Analysis Of Depression, Stress, and Anxiety Levels Based On Dass (Depression Anxiety Stress Scale) 42 in North Sulawesi - Sepron Adam, Rahmat; Sembiring, Utari; Naomi Shinta, Krisma; Rangga Wijaya, Abimanyu; Palii, Cicilia (Labor Program Studi Pendidikan Sosiologi, 2024)
Someone who's trapped in online loan debt usually tends to experience some psychological pressure that attacks their mental health such as depression, stress, and anxiety. These pressures come from many different factors in online loans, like the coercion by the debt collector and even the fear of not being able to pay off the debt. According to the Indonesian Financial Services Authority (OJK), the usage of online loan services in North Sulawesi in 2023 growing up to 61,81% with the growth amounting to IDR 435,52 billion. Growing from 2016-2022 the total distribution reached IDR 2,17 trillion, with a total of 484.555 borrowers and 5.014 accounts as lenders. The amount of online loan services is inseparable from the presence of illegal online loans that harm society. The purpose of this research is to find out the level of depression, stress, and anxiety of the online loan victim. We started this research from July until November 2023. We gathered the data from 44 respondents, aged between 17 to 35 years old in North Sulawesi. Using DASS-42 as the psychological measuring tool, all questions were answered directly by the respondents with the accompaniment of the researcher and followed by statistical analysis. The result of this research has found that online loan customers experience depression, anxiety, and stress regardless of what services they use whether it's legal or illegal. Based on this research, we discover that most of the online loan customers are experiencing normal depression (75%), normal stress (65,9%), and normal anxiety (36,4%).